Организация и методика массовой физической культуры борцов - Абдуллаев, А.; Abdulaev, A. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
В данной статье раскрываются показатели состояния физической культуры, фазы восстановительного периода после тренировки, основной фактор, определяющий деятельность борцов. This article shows indices of the physical culture state, phases of restoration period after training and the main factor that determines wrestler’s activity.
Organization and Methodology of Wrestler’s Mass Physical Culture
Keywords: спорт; спортивная борьба; эффективность подготовки; восстановительные средства; массовость; правила; методика отбора; sports; wrestling; training efficiency; rehabilitation facilities; mass; rules; methods of selection